Something hidden behind the ranges - Taylor-Ide, Daniel (Mercury House, 1995)
Beginning with a search for Yeti, the abominable snowman, or Big-Foot, Taylor-Ide gradually came to believe that what's most important in the Himalayas is to protect the rare environment so that whatever lives there may continue.